Erratology of russian speech in the media space (Eurasian Journal of Philology Science and Education, 2024)
The relevance of this work is due to the fact that recently the mistakes made by bilingual Kazakhs in the media space have become more frequent. Based on such texts, the level of culture of the addressee and their upbringing are determined. This trend does not leave linguist teachers indifferent. Therefore, together with first and second year students of the Kazakh National Academy of Arts. T.K. Zhurgenov, the author, carried out the “Elimination of illiteracy” project, as a result of which errors in the media space were studied. The purpose of this work is a comprehensive analysis of deviations from the norm in Russian speech. To explore the issue in more detail, the researcher uses the concepts of “deviation,” “erratology,” and “errative component.” The term “deviation” includes deviation from the norm of the language system, in communication, in speech practice and takes a position from the norm to the error. Erratology, in turn, as the science of errors, allows you to classify errors, qualify them by the nature of their formation, as well as their correction. The author used a scaling method consisting of an increasing number of 15 errative components, each of which includes typical deviations and errors. This method can be useful in language teaching methods. The project gave students the opportunity to independently find errors in texts, analyze them, and also repeat spelling rules.Keywords: еrratology, deviation, errative component, bilingualism, error.